2019
DOI: 10.1016/j.bpj.2018.11.3128
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Protein-free Membrane Fusion: A Giant Vesicle Study

Abstract: Membrane fusion is a ubiquitous process in biology and is a prerequisite for many intracellular delivery protocols relying on the use of liposomes as drug carriers. Here, we investigate in detail the process of membrane fusion and the role of opposite charges in a protein-free lipid system based on cationic liposomes (LUVs, large unilamellar vesicles) and anionic giant unilamellar vesicles (GUVs) composed of different palmitoyloleoylphosphatidylcholine (POPC)/palmitoyloleoylphosphatidylglycerol (POPG) molar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 89 publications
(135 citation statements)
references
References 93 publications
12
118
1
Order By: Relevance
“…In some of the examples fusion has led to spontaneous budding, correlating to predictions made by theoretical models, [91] which has been put in the context of growth and division cycles for self-reproduction. [118] In contrast, when mediated by high charge density, the fusion of positively charged liposomes induces extensive area increase of the negative GUVs [89,119] (see also Figure 2D). [112] Membrane fusion of small liposomes has been used for decades [113,114] and only more recently fusion using giant vesicles has been reported.…”
Section: Growth Via Vesicle Fusionmentioning
confidence: 97%
See 2 more Smart Citations
“…In some of the examples fusion has led to spontaneous budding, correlating to predictions made by theoretical models, [91] which has been put in the context of growth and division cycles for self-reproduction. [118] In contrast, when mediated by high charge density, the fusion of positively charged liposomes induces extensive area increase of the negative GUVs [89,119] (see also Figure 2D). [112] Membrane fusion of small liposomes has been used for decades [113,114] and only more recently fusion using giant vesicles has been reported.…”
Section: Growth Via Vesicle Fusionmentioning
confidence: 97%
“…[95] The latter observation was ascribed to the low amount of product due to the limited encapsulation, which will be difficult to overcome unless efficient transport mechanisms for the various precursors are established. [89] The change occurs within seconds. [96] Although the authors did not specifically follow the vesicle growth, they identified practical barriers causing the low lipid synthesis rate, speculated about transport mechanisms for acyl-CoA, and discussed relevant crowding and confinement effects.…”
Section: Growth Via Uptake Of Synthesized Membrane Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, Shiomi et al showed that electrofusion can be achieved in a closed microfluidic device but the setup also required the use external optical traps for vesicle selection/positioning. [88] In this work, microfluidic valves allow rapid and real-time monitoring of the fusion events (see Figure 3e). [67,87,92] Positioning of the vesicles relative to the electrodes is achieved either by alignment using the electric field itself, [67] growing them on the electrodes, [92] or trapping in PDMS posts.…”
Section: Membrane Fusionmentioning
confidence: 98%
“…[85] They also showed that GUVs containing a simple set of cytoskeletal proteins Adv. [88] Copyright 2019, Elsevier. 2019, 3, 1800318 [36] Copyright 2014, American Chemical Society.…”
Section: Growthmentioning
confidence: 99%